2001
DOI: 10.1093/gerona/56.5.b209
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Muscle Strength Changes in Older Adults: Influence of Muscle Mass, Physical Activity, and Health

Abstract: The longitudinal changes in isokinetic strength of knee and elbow extensors and flexors, muscle mass, physical activity, and health were examined in 120 subjects initially 46 to 78 years old. Sixty-eight women and 52 men were reexamined after 9.7 +/- 1.1 years. The rates of decline in isokinetic strength averaged 14% per decade for knee extensors and 16% per decade for knee flexors in men and women. Women demonstrated slower rates of decline in elbow extensors and flexors (2% per decade) than men (12% per deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

35
506
5
38

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 749 publications
(584 citation statements)
references
References 31 publications
35
506
5
38
Order By: Relevance
“…They found percent changes per year of −2.56 ± 1.1 % in isokinetic strength of the knee extensors at 60°/s and −4.2 ± 1.2 % at 240°/s, but this study only considered 12 subjects (five men) (Frontera et al 2008). Hughes et al (2001) found declines in isokinetic speed at 60°/s of −1.18 ± 1.55 % in women and −1.45 ± 1.56 % in men, which is more in line with our results (Hughes et al 2001). Their reported percent change per year is still larger, but it is probably explained by the older age range of their sample (46 to 78 years), whereas we considered subjects between 19 and 73 years old (baseline) (Hughes et al 2001).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…They found percent changes per year of −2.56 ± 1.1 % in isokinetic strength of the knee extensors at 60°/s and −4.2 ± 1.2 % at 240°/s, but this study only considered 12 subjects (five men) (Frontera et al 2008). Hughes et al (2001) found declines in isokinetic speed at 60°/s of −1.18 ± 1.55 % in women and −1.45 ± 1.56 % in men, which is more in line with our results (Hughes et al 2001). Their reported percent change per year is still larger, but it is probably explained by the older age range of their sample (46 to 78 years), whereas we considered subjects between 19 and 73 years old (baseline) (Hughes et al 2001).…”
Section: Discussionmentioning
confidence: 88%
“…Hughes et al (2001) found declines in isokinetic speed at 60°/s of −1.18 ± 1.55 % in women and −1.45 ± 1.56 % in men, which is more in line with our results (Hughes et al 2001). Their reported percent change per year is still larger, but it is probably explained by the older age range of their sample (46 to 78 years), whereas we considered subjects between 19 and 73 years old (baseline) (Hughes et al 2001). However, if we only considered subjects above 46 years of age, Δ percentage/year was −0.96 ± 2.16 % in women and −0.77 ± 2.28 % in men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the correlations between muscle mass and strength, physical function, and quality of life did not obtain significance in patients with vertebral fracture. Possibly poor muscle quality, poor neural recruitment, or reduced effort may influence poor physical functioning in these patients (40,41). Consistent with the latter explanation was the finding that self-reported pain, one of the domains of the SF-36 quality of life questionnaire, was correlated with both muscle strength and physical functioning in patients with vertebral fracture.…”
Section: Discussionmentioning
confidence: 63%
“…Previous longitudinal studies have reported selection of the study population to healthier and more mobile subjects (Aniansson et al 1983;Rantanen et al 1997;Rantanen and Heikkinen 1998;Hughes et al 2001;Paterson et al 2004). The selection bias will lead to underestimations of the performance and fitness changes with aging (Rantanen et al 1997), and will cause the population estimates of physical performance, if used as norm reference values, to be too high.…”
Section: Introductionmentioning
confidence: 99%